Natural Compounds and Biopolymers-Based Hydrogels Join Forces to Promote Wound Healing - Federica Falbo; Umile Gianfranco Spizzirri; Donatella Restuccia; Francesca Aiello (MDPI AG, 2023)
Rapid and complete wound healing is a clinical emergency, mainly in pathological conditions such as Type 2 Diabetes mellitus. Many therapeutic tools are not resolutive, and the research for a more efficient remedial remains a challenge. Wound dressings play an essential role in diabetic wound healing. In particular, biocompatible hydrogels represent the most attractive wound dressings due to their ability to retain moisture as well as ability to act as a barrier against bacteria. In the last years, different functionalized hydrogels have been proposed as wound dressing materials, showing encouraging outcomes with great benefits in the healing of the diabetic wounds. Specifically, because of their excellent biocompatibility and biodegradability, natural bioactive compounds, as well as biomacromolecules such as polysaccharides and protein, are usually employed in the biomedical field. In this review, readers can find the main discoveries regarding the employment of naturally occurring compounds and biopolymers as wound healing promoters with antibacterial activity. The emerging approaches and engineered devices for effective wound care in diabetic patients are reported and deeply investigated.